A review on additive manufacturing of polymer-fiber composites. (15th December 2017) - Parandoush, Pedram; Lin, Dong
Abstract: Additive manufacturing (AM) of polymer-fiber composites has transformed AM into a robust manufacturing paradigm and enabled producing highly customized parts with significantly improved mechanical properties, compared to un-reinforced polymers. Almost all commercially available AM methods could benefit from various fiber reinforcement techniques. Recent developments in 3D printing methods of fiber reinforced polymers, namely, fused deposition modeling (FDM), laminated object manufacturing (LOM), stereolithography (SL), extrusion, and selective laser sintering (SLS) are reviewed in this study to understand the trends and future directions in the respective areas. In addition to extra strength, fibers have also been used in 4D printing to control and manipulate the change of shape or swelling after 3D printing, right out of the printing bed. Although AM of fiber/polymer composites are increasingly developing and under intense attention, there are some issues needed to be addressed including void formation, poor adhesion of fibers and matrix, blockage due to filler inclusion, increased curing time, modelling, simulation, etc. Nonetheless, numerous innovative techniques were spotted amongst recent work trying to overcome these challenges with new material or manufacturing techniques.